A comparison of measured and modeled velocity fields for a laminar flow in a porous medium. (November 2015) - Wood, B.D.; Apte, S.V.; Liburdy, J.A.; Ziazi, R.M.; He, X.; Finn, J.R.; Patil, V.A.
Highlights: High-resolution particle imaging velocimetry measurements of velocity were collected. Measurements were compared with numerical simulations on the experimental geometry. Good fidelity between results was achieved. REV size and error estimates for measurements are reported. Hydraulic conductivity estimates were computed. Abstract: Obtaining highly-resolved velocity data from experimental measurements in porous media is a significant challenge. The goal of this work is to compare the velocity fields measured in a randomly-packed porous medium obtained from particle image velocimetry (PIV) with corresponding fields predicted from direct numerical simulation (DNS). Experimentally, the porous medium was comprised of 15 mm diameter spherical beads made of optical glass placed in a glass flow cell to create the packed bed. A solution of ammonium thiocyanate was refractive-index matched to the glass creating a medium that could be illuminated with a laser sheet without distortion. The bead center locations were quantified using the imaging system so that the geometry of the porous medium was known very accurately. Two-dimensional PIV data were collected and processed to provide high-resolution velocity fields at a single plane within the porous medium. A Cartesian-grid-based fictitious domain approach was adopted for the direct numerical simulation of flow through the same geometry as the experimental measurements and without any adjustable parameters. The uncertainties associated with characterization of the pore geometry, PIV measurements, and DNS predictions were all systematically quantified. Although uncertainties in bead position measurements led to minor discrepancies in the comparison of the velocity fields, the axial and normal velocity deviations exhibited normalized root mean squared deviations ( NRMSD ) of only 11.32% and 4.74%, respectively. The high fidelity of both the experimental and numerical methods have significant implications for understanding and even for engineering the micro–macro relationship in porous materials. The ability to measure and model sub-pore-scale flow features also has relevance to the development of upscaled models for flow in porous media, where physically reasonable closure models must be developed at the sub-pore scale. These results provide valuable data in support of that goal.